Critical assessment of the impact of operation condition on the determination of a ship main propulsion power - Leow, Wei Chi (Nanyang Technological University, 2020)
This report focuses on an analysis of the fuel consumption performance of ship sailing in a seaways by use of on-board monitored data of an oil/chemical tanker. The data examined by an austere analysis method, supported by external weather data from Wave Watch III hindcast. The comparison will be made with the prediction results formulated with Microsoft Excel and an online software, TIBCO Spotfire. This method can be incorporated into a decision support system to access the hull/propeller performance of a ship.